Pengaruh Sosial Ekonomi Keluarga Terhadap Kejadian Stunting di Desa Parsibarungan Kecamatan Pangaribuan Kabupaten Tapanuli Utara - Yuli Harum Mayarli Sidabutar; Malida putri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Study this discuss about influence social economy family with Stunting incident in the District Pangaribuan Regency North Tapanuli. Stunting is condition fail grow a child consequence infection nutrition recurrent ( chronic ) so that child more short from friend her age. The stunting indicator is seen from tall body age (TB/U) if z-score value <-2SD is said short and said very short if z-score value <-3SD. Study this conducted with destination for knowing how much big influence social economy family with Stunting incident, District Pangaribuan Regency North Tapanuli. Method study this use Spearman Rank Correlation with approach quantitative. Technique withdrawal sample on study this is saturated sampling where all member population used as sample, then sample study this is all family with child stunting incident in the village Parsibarungan Subdistrict Pangaribuan Regency North Tapanuli, totaling 24 families. Results study with analysis Spearman Rank test obtained score significance Among social economy family with stunting incidence of 0.000 or more small from 0.05 so that, Ha is accepted and Ho is rejected which shows existence significant influence Among social economy family with stunting incident. Based on results testing then know score coefficient Spearman Rank correlation is 0.739 which means there is high influence and strong.